A Wide-field Map of Ultracompact Dwarfs in the Coma Cluster - Richard T. Pomeroy; Juan P. Madrid; Conor R. O’Neill; Alexander T. Gagliano (The Astrophysical Journal)
A data set of 23,351 globular clusters (GCs) and ultracompact dwarfs (UCDs) in the Coma cluster of galaxies was built using Hubble Space Telescope Advanced Camera for Surveys data. Based on the standard magnitude cut of M _V ≤ −11, a total of 523 UCD candidates are found within this data set of compact stellar systems (CSS). From a color–magnitude diagram analysis built using this catalog, we find a clear mass–magnitude relation extending marginally into the UCD parameter space. The luminosity function defined by this data set shows an excess of sources at bright magnitudes, suggesting a bimodal formation scenario for UCDs. We estimate the number of UCDs with a different origin than GC to be N _UCD ≳ 32 ± 1. We derive the total number of CSS within the core (1 Mpc) of Coma to be N _CSS ≈ 69,400 ± 1400. The radial distribution of UCDs in Coma shows that, like GCs, UCDs agglomerate around three giant ellipticals: NGC 4874, NGC 4889, and IC 4051. We find UCDs are more centrally concentrated around these three ellipticals than GCs. IC 4051 has a satellite population of UCDs similar to NGC 4874 and NGC 4889. We estimate only ∼14% of UCDs inhabit the intracluster space (ICUCD) between galaxies in the region, in comparison to ∼24% for GCs (ICGC). We find red (metal-rich) UCDs are more likely located closer to a host galaxy, with blue (metal-poor) UCDs showing a greater dispersion and lower average density in the region.